Wetland Environments: A Global Perspective - Aber J. S. James Sandusky (Chichester, Wiley-Blackwell, 2012)
A complete study of wetland environments requires the assessment of their physical and biological attributes, properties and functions of these ecosystems, and the economic, political and social aspects that mediate their use globally. A systems approach is taken throughout this book which emphasizes the interactions between these elements of wetland ecosystems. Moreover, selected case studies from across the world are used to illustrate wetland characteristics and circumstances. This book is intended to foster a greater awareness and appreciation of wetlands, promote a culture of conservation and wise management, and spread the knowledge that wetlands are important, indeed crucial, elements of the global environment. Our attempts to understand, manage and enhance wetlands in the twenty-first century are part of the larger effort to maintain a sustainable Earth. Readership: Undergraduate and graduate students worldwide studying wetland environments, as well as researchers and applied environmental scientists involved in wetland ecology and conservation.